1988
DOI: 10.1042/bj2560053
|View full text |Cite
|
Sign up to set email alerts
|

Specific accumulation of 17α-hydroxyprogesterone in microsomal membranes during the process of cytochrome P-450(C-17)-catalysed androgen biosynthesis. A dynamic study of intermediate formation and turnover

Abstract: A complete dynamic analysis of cytochrome P-450(C-17)-catalysed androgen biosynthesis from a single dose of progesterone and 17 alpha-hydroxyprogesterone in a double-label double-substrate experiment was performed in order to elucidate the controversial intermediacy of 17 alpha-hydroxyprogesterone. Label distribution within the steroid fractions as well as in the membrane and buffer compartments yields direct evidence that the endogenously formed 17 alpha-hydroxyprogesterone (which is in an 'intermediate state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1989
1989
1995
1995

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The phenomenon of channeling has also been described for P-45OI,, (Eckstein et al, 1987;Kiihn-Velten et al, 1988;Yamazaki et al, 1992), for P-450,,, (Burstein and Gut, 1976), for P-450,,,, (Kelly et al, 1977) and additionally for non-steroidogenic cytochrome P-450 such as P-450, (Swinney et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of channeling has also been described for P-45OI,, (Eckstein et al, 1987;Kiihn-Velten et al, 1988;Yamazaki et al, 1992), for P-450,,, (Burstein and Gut, 1976), for P-450,,,, (Kelly et al, 1977) and additionally for non-steroidogenic cytochrome P-450 such as P-450, (Swinney et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…In some systems, the accumulation of intermediates has been proposed to depend on the degree of multienzyme complex organization and the actual metabolic situation [8,9,37,41,42,54]. As to the nature of intermediates in sex steroid biosynthetic processes, the possible alternatives, whether intermediates are truly enzyme-bound, whether they are by-products of transient, labile enzyme-bound states, or whether they represent leaky pathways resulting from steroid transfer between active centres of enzymes, are controversely discussed [ 5,18,24,27,28,[33][34][35][36]551. Some clarification has emerged from a recent study [5] showing that 17ahydroxyprogesterone, the intermediate within the P450XVII-catalysed progesterone to androstenedione conversion, can be specifically retained in endoplasmic reticulum membranes if being in the transient state, but that it is likewise able to leave and to re-enter the membrane-associated intermediary 1 7a-hydroxyprogesterone pool.…”
Section: Discussionmentioning
confidence: 99%
“…The hydroxylated intermediates of the steroidogenic P450-catalysed concerted hydroxylation and cleavage reactions are mainly present in an enzyme-bound state and specifically retained in the membrane compartments though some leakage from the enzyme and the membrane phase seems to be possible [5,18,24,. The degree of such intermediate leakage is much higher in the P45OXVII system than in the P450XI or P45OXIX systems [2,5,28,34,36] but has rarely been subjected to a complete quantitative analysis.…”
Section: Control Of Intermediate Leakage From Cytochrome P450 Jcb151mentioning
confidence: 99%
See 1 more Smart Citation
“…When the Iyophilized pellet is reintroduced into the aqueous incubation medium, the altered state is retained and the substrate is able to enter into the steroidogenic factories. Earlier workers (14)(15)(16) have suggested that, when adrenal mitochondria (obtained by ultracentrifugation) are used as an enzyme source, exogenously added cholesterol is converted only to C2102 metabolites because the pregnenolone formed is retained in the membrane microenvironment of the cytochrome P450 site and is therefore unable to proceed to the site where the next enzymatic process occurs. Disruption of this microenvironment by lyophilization (as well as by subsequent washing with solvents to remove lipids) could be a factor in allowing the further metabolism of the in situ intermediate (presumably pregnenolone) by enzymes in the 12,000 x g pellet.…”
Section: Discussionmentioning
confidence: 99%